2001
DOI: 10.1074/jbc.m010612200
|View full text |Cite
|
Sign up to set email alerts
|

The Binding of Oxidized Low Density Lipoprotein (ox-LDL) to ox-LDL Receptor-1 Reduces the Intracellular Concentration of Nitric Oxide in Endothelial Cells through an Increased Production of Superoxide

Abstract: Endothelium-dependent relaxation is impaired in animals with atherosclerosis (1-3), which has been linked to a decreased production and/or biological activity of endotheliumderived nitric oxide (NO) 1 (4, 5). Oxidative inactivation of NO is regarded as an important cause of its decreased biological activity (6). The vascular release of superoxide (O 2 . ) radicals is sharply increased in atherosclerotic arteries (7,8), and O 2 . is known to inactivate NO in a chemical reaction during which the cytotoxic radica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
228
2
7

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 327 publications
(243 citation statements)
references
References 58 publications
6
228
2
7
Order By: Relevance
“…Incubation with ox-LDL also induced the increased production of intracellular superoxide anion and hydrogen peroxide, which was also mediated by LOX-1 (Cominacini et al 2000(Cominacini et al , 2001. It has also been shown that the binding of ox-LDL to LOX-1 decreases intracellular nitric oxide levels through an increased production of superoxide anion, which could inactivate nitric oxide (Cominacini et al 2001). Both superoxide anion and hydrogen peroxide are products of LOX-1 activation and inducers of LOX-1 expression (Nagase et al 2001).…”
Section: X-p Chen Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Incubation with ox-LDL also induced the increased production of intracellular superoxide anion and hydrogen peroxide, which was also mediated by LOX-1 (Cominacini et al 2000(Cominacini et al , 2001. It has also been shown that the binding of ox-LDL to LOX-1 decreases intracellular nitric oxide levels through an increased production of superoxide anion, which could inactivate nitric oxide (Cominacini et al 2001). Both superoxide anion and hydrogen peroxide are products of LOX-1 activation and inducers of LOX-1 expression (Nagase et al 2001).…”
Section: X-p Chen Et Almentioning
confidence: 99%
“…Most of the information about the signal transduction pathways of LOX-1 came from the activation or inhibition of LOX-1 by ox-LDL and LOX-1 antibody. Using bovine aortic endothelial cells and CHO-K1 cells transfected with the LOX-1 gene (LOX-1-CHO-K1), Cominacini et al (2000Cominacini et al ( , 2001 revealed that the binding of ox-LDL to LOX-1 induces a sharp increase of intracellular reactive oxygen species (ROS) production determined by 2 ,7 -dichlorofluorescein diacetate (DCFH 2 -DA) assay as early as 5 minutes after the start of incubation with ox-LDL. Native LDL (nLDL), acetylated LDL (Ac-LDL) and malondialdehyde-modified LDL (MDA-LDL) show no effect.…”
Section: Signal Transduction Pathways Of Lox-1mentioning
confidence: 99%
“…Endothelial cell dependent relaxation of vascular smooth muscle cells (SMC) is impaired in atherosclerosis (Cominacini et al 2001) due to decreased availability of nitric oxide (NO). Reduction in NO availability may result in an additional down-regulation of NO formation, though this is still controversial (Ignarro 1990 ).…”
Section: Atherosclerosismentioning
confidence: 99%
“…NADPH oxidase, NOS to a lesser extent, and xanthine oxidase are implicated in increased ROS in endothelial cells upon exposure to minimally oxidized LDL (oxLDL, (Heinloth et al 2000;Cominacini et al 2001;Rueckschloss et al 2001;Stepp et al 2002). NADPH oxidase is also an important contributor to O 2 ·-levels in smooth muscle cells due to H 2 O 2 exposure ).…”
Section: Nos (Enos) and Inducible Nos (Inos) In Addition There Is Tmentioning
confidence: 99%
“…The expression of LOX-1 is induced by stimuli as rapidly as other kinds of cell-adhesion molecules and selectins, suggesting that LOX-1 is in the so-called class of immediate early genes. LOX-1 is a potent mediator of ''endothelial dysfunction'': binding of endothelial LOX-1 by ligands induces superoxide generation, inhibits nitric oxide production, enhances endothelial adhesiveness for leukocytes, and induces expression of chemokines (14)(15)(16). The versatile activities of LOX-1 include the ability to bind not only oxidized LDL, but also aged red blood cells, apoptotic cells, and activated platelets (17,18).…”
mentioning
confidence: 99%